Optimization of zero-valent iron activated persulfate treatment of liquor wastewater by response surface method - CHEN Yongshuang; FANG Wei; LI Siyang; LUO Qijin; XIE Gang; WU Zexuan; WANG Yilin; LI Jingshi (Gongye shui chuli, 2024)
The effluent from the secondary sedimentation tank of the wastewater treatment plant of a liquor production enterprise in Guizhou was taken as the research object. Zero-valent iron（Fe0） activated persulfate（S2O82-，PS） advanced oxidation method was used to further treat the effluent，and the process conditions were optimized. The effects of initial pH，PS dosage and molar ratio of Fe0 to PS on the treatment effect of liquor wastewater were investigated by single factor experiment，and the process conditions were further optimized by response surface method. The results show that persulfate process can effectively reduce the organic content of liquor wastewater. The optimal process conditions are as follows：initial pH is 4.08，The PS dosage was 1.39 times the theoretical dosage （1 mg/L COD complete oxidation theoretically requires 12 mg/L PS），n（Fe0）∶n（PS）=1.27. Under these conditions，the COD removal rate of liquor wastewater reaches 70.33%.